The ephemeral development of C′ shear bands: A numerical modelling approach. (October 2020) - Finch, M.A.; Bons, P.D.; Steinbach, F.; Griera, A.; Llorens, M.-G.; Gomez-Rivas, E.; Ran, H.; de Riese, T.
Abstract: C′ shear bands are ubiquitous structures in shear zones but their development is poorly understood. Previous research has determined they mostly occur in rocks with a high mechanical strength contrast. Using numerical models of viscoplastic deformation, we studied the effect of the proportion of weak phase and the phase strength contrast on C′ shear band development during simple shearing to a finite strain of 18. We found that C′ shear bands form in models with ≥5% weak phase when there is a moderate or high phase strength contrast, and they occur in all models with weak phase proportions ≥15%. Contrary to previous research, we find that C′ shear bands form when layers of weak phase parallel to the shear zone boundary rotate forwards. This occurs due to mechanical instabilities that are a result of heterogeneous distributions of stress and strain rate. C′ shear bands form on planes of low strain rate and stress, and not in sites of maximum strain rate as has previously been suggested. C′ shear bands are ephemeral and they either rotate backwards to the C plane once they are inactive or rotate into the field of shortening and thicken to form X- and triangle-shaped structures. Highlights: C′ shear bands are an important microstructure in ductile shear zones. We show that C′ shear bands form when layers of weak minerals rotate forwards. C′ shear bands become inactive when they rotate backwards or shorten and collapse. To form C′ shear bands at least 5–15% weak phase is needed. The amount of weak phase required depends on the strength contrast between minerals.